2012
DOI: 10.5039/agraria.v7i3a1402
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura e dinâmica da vegetação em um remanescente de Floresta Atlântica/Nordeste, Brasil

Abstract: RESUMO O efeito de borda causa uma série de alterações na estrutura da vegetação, microclima, dinâmica e composição de espécies, tornando esse ambiente bastante distinto do interior. Neste trabalho, foi analisada a influência da distância do limite florestal na estrutura e dinâmica (2006 e 2009) do dossel e do sub-bosque de um fragmento com 14 ha localizado na Floresta Atlântica em Igarassu, PE. A borda externa, formada há cerca de 35 anos, foi definida do limite florestal até 50 m, o ambiente intermediário de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…In addition, due to the similarity of the edge habitats, it is likely that only the best performing subset of pioneers will dominate the edge habitats throughout the landscape. Although some studies have found a higher diversity in edges than in the corresponding interior [82,83] we believe, in view of the large number of recent studies and reviews [15,28,[84][85][86] that support our findings, that the opposite might be the usual pattern in forest fragments, at least in tropical southeast Brazil. A higher diversity of edge habitats may exist shortly after edge creation, when some elements of the original tree flora are still present, although not reproducing, and pioneer species are beginning to proliferate [77,87].…”
Section: Patterns and Underlying Mechanismssupporting
confidence: 75%
“…In addition, due to the similarity of the edge habitats, it is likely that only the best performing subset of pioneers will dominate the edge habitats throughout the landscape. Although some studies have found a higher diversity in edges than in the corresponding interior [82,83] we believe, in view of the large number of recent studies and reviews [15,28,[84][85][86] that support our findings, that the opposite might be the usual pattern in forest fragments, at least in tropical southeast Brazil. A higher diversity of edge habitats may exist shortly after edge creation, when some elements of the original tree flora are still present, although not reproducing, and pioneer species are beginning to proliferate [77,87].…”
Section: Patterns and Underlying Mechanismssupporting
confidence: 75%
“…On this scale, the reduced area favors lower heterogeneity due to the more similar physical conditions (light, water, soil, etc.) (Costa et al, 2012). On the other hand, on larger area size entails greater environmental heterogeneity (Cavender-Bares et al, 2009).…”
Section: Ratesmentioning
confidence: 99%
“…Little data has been gathered from the extremely fragmented Brazilian Atlantic coastal forest in the northeastern region of that country (Oliveira et al, 2004;Santos et al, 2008). Laurance et al (1998a) reported greater tree mortality along the forest border than in the interior of 10 and 100 ha fragments in the Amazon region, while mortality and recruitment in both the canopy and understory were found to be similar along the border and in the interior of 14 (Costa et al, 2012) -which could have resulted from the homogenization of the vegetation in those highly fragmented sites .…”
Section: Introductionmentioning
confidence: 99%